2020
DOI: 10.1177/0194599820907600
|View full text |Cite
|
Sign up to set email alerts
|

High‐Frequency Conductive Hearing following Total Drum Replacement Tympanoplasty

Abstract: Objectives Conventional reporting of posttympanoplasty hearing outcomes use a pure-tone averaged air-bone gap (ABG) largely representing a low-frequency sound conduction. Few studies report high-frequency conductive hearing outcomes. Herein, we evaluate high-frequency ABG in patients following temporalis fascia total drum replacement. Study Design Case series with chart review. Setting Tertiary care center. Subjects and Methods All patients who underwent type 1 tympanoplasty using a lateral graft total drum re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
21
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 12 publications
(24 citation statements)
references
References 28 publications
2
21
1
Order By: Relevance
“…By utilizing a low‐frequency biased PTA calculation, traditional reporting methods do not recognize both the persistent high‐frequency conductive deficits following ossiculoplasty and the significantly different magnitude of ABG improvement between high and low frequencies. Likewise, published data of our own demonstrate similar discrepancies between traditional and frequency‐specific reporting of audiometric outcomes in patients undergoing type 1 tympanoplasty 17 …”
Section: Discussionsupporting
confidence: 69%
“…By utilizing a low‐frequency biased PTA calculation, traditional reporting methods do not recognize both the persistent high‐frequency conductive deficits following ossiculoplasty and the significantly different magnitude of ABG improvement between high and low frequencies. Likewise, published data of our own demonstrate similar discrepancies between traditional and frequency‐specific reporting of audiometric outcomes in patients undergoing type 1 tympanoplasty 17 …”
Section: Discussionsupporting
confidence: 69%
“…Our secondary analysis of the results from over 700 patients published by Pauli 2019 shows a more complete closure of the ABG at low frequencies than high frequencies with similar magnitudes to our data set. Our prior work on high‐frequency conductive hearing following middle ear surgery 9 , 10 suggests that across middle ear surgical procedures, post‐operative high frequency ABGs persist and may be under‐reported using current PTA 4 standards. 8 …”
Section: Discussionmentioning
confidence: 99%
“…A 2018 review by Cheng et al, demonstrated the short and long‐term durability of hearing improvements following stapedotomy using PTA data from several published series 6 . However, the traditional pure‐tone average (PTA 4 ) recommended by the American Academy of Otolaryngology‐Head and Neck Surgery (AAO‐HNS), 7,8 may not sufficiently communicate changes in high‐frequency (HF) conductive hearing 9,10 . HF bone conduction thresholds following stapes surgery have not been robustly studied and reported outcomes are variable 5,11‐13 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…3,4,8-11 Literature reports that for the majority of patients, postoperative air-bone gap (ABG) is >10 dB and on average ~15 dB. 3,4,6,7,10,11 Interestingly, studies demonstrate frequency-dependent hearing outcomes with the lack of improvement in the high-frequency ranges, 10-12 possibly due to specific graft materials. 12-14…”
mentioning
confidence: 99%